Clinical Trajectories at the End of Life in Autopsy-Confirmed Dementia Patients With Alzheimer Disease and Lewy Bodies Pathologies - Gu, Yian; Kociolek, Anton; Fernandez, Kayri K; Cosentino, Stephanie A; Zhu, Carolyn Wei; Jin, Zhezhen; Leverenz, James B; Stern, Yaakov B (Neurology, 2022)
Evaluating and understanding the heterogeneity in dementia course has important implications for clinical practice, health care decision-making, and research. However, inconsistent findings have been reported with regard to the disease courses of the 2 most common dementias: Alzheimer disease (AD) and dementia with Lewy bodies (DLB). Using autopsy-confirmed diagnoses, we aimed to examine the disease trajectories in the years before death among patients with dementia with pure AD, pure DLB, or mixed (AD and DLB) pathologies. The current retrospective longitudinal study included 62 participants with autopsy-confirmed diagnoses of pure AD (n = 34), mixed AD and DLB (AD + DLB; n = 17), or pure DLB (n = 11) from the Predictors 2 Cohort Study, a prospective, clinic-based, cohort of patients with dementia. Generalized estimating equation models, with time zero at death, were used to examine the trajectory of cognition (Folstein Mini-Mental State Examination [MMSE]), function (activities of daily living [ADL]), and Dependence Scale among patients with different autopsy-confirmed diagnosis (pure AD, AD + DLB, and pure DLB). The models were adjusted for age, sex, education, and baseline features including extrapyramidal signs, MMSE, ADL, and Dependence Scale. The participants on average received 9.4 ± 4.6 assessments at 6-month intervals during a mean 5.4 ± 2.9 years of follow-up. The 3 groups were similar in both cognition and function status at baseline. Cognition and function were highly correlated among patients with AD + DLB but not in pure AD or pure DLB at baseline. Patients of the 3 groups all declined in both cognition and function but had different trajectories of decline. More specifically, the patients with pure DLB experienced approximately double the rate of both cognitive decline and functional decline than the patients with pure AD, and the mixed pathology group showed double the rate of functional decline as compared to pure AD. In this longitudinal study, we found that among patients with dementia, those with Lewy body pathology experienced faster cognitive and functional decline than those with pure AD pathology.